THE TRANSFORMATION OF PESANTREN TAHFIDZ AL QUR’AN EDUCATIONAL MANAGEMENT - Priyatno, Agus (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The research purpose is to describe the transformation of education management which focus is on memorizing Al Qur’an in Jawa Tengah. The research is qualitative of ethnographic approach to observe the Pesantren Yanbu’ul Qur’an Arwaniyyah Kudus in Central Java which had been conducted in 2016.Data were collected by a series of observations, in-depth interviews and document analysis and archival research. The uniqueness and the consistency in memorizing Al Qur’an can be clearly seen from a series of transformation to the learning system such as its curriculum, methods, materials, teachers, media and evaluation system. Institutional development is in accordance with the type of the Pesantren, education level and management cooperation which expectation is to be able to serve students from a wide segmentation. Predominance leadership style relies on the charismatic Kyai as delegated to the Pesantren institutional unit leadership system and professional assistances.ThePesantren able to manage such transformation without sacrificing the character as a traditional pesantren well known for its special culture as an institution in which knowledge of Islam is transmitted and transferred, Islam values and tradition reservation and ulema reproduction. Keywords: Pesantren, Reciter, Tranformation, Education Management